(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article provides a comprehensive overview of the agricultural techniques for growing sweet corn at home. These methods serve to increase the yield of corn, improve its quality and taste. The study provides information on soil preparation, seed selection, crop care, irrigation and fertilization technologies. Measures to combat diseases and pests are also covered. With the help of these measures, it is possible to grow effective and high-yielding sweet corn at home.